Gambaran Sikap Ibu Terhadap Pemberian Asi Eksklusif Pada Pasca Pandemi Covid-19 Di Puskesmas Kassi-Kassi Kota Makassar Tahun 2023 - Noviyani Hartuti; Yoan Putri Praditia Susanto (JURNAL KESEHATAN DELIMA PELAMONIA, 2023)
Exclusive breastfeeding begins within one hour after the baby is born until the baby is 6 months old. Early Initiation of Breastfeeding (IMD) can help children survive and have the antibodies the body needs to avoid various common diseases, such as pneumonia and diarrhea. Central Statistics Agency (BPS, 2021) data from 2019 to 2021 states that the percentage of babies aged less than 6 months who receive exclusive breastfeeding according to South Sulawesi Province continues to increase every year, namely in 2019 it was 70.52%, in 2020 it was 76.21% and in 2021 it was 76.43%. Analysis of Indonesian Covid-19 data updated as of November 18 2022. Currently there are 6,596,812 confirmed patients, 6,376,205 patients have recovered and 158,323 people have died. The current active cases of Covid-19 in Indonesia are 61,284 people with 6,207 suspects having been examined (Sebaran, 2022). To get an idea of a mother's attitude towards giving exclusive breastfeeding to babies during the post-Covid-19 pandemic at the Kassi-Kassi Health Center, Makassar City in 2022. The method used in this research is a quantitative method with a descriptive approach. The results of this study indicate that the description of mothers' attitudes towards exclusive breastfeeding during the Covid-19 pandemic at the Kassi-Kassi health center in Makassar City is good by looking at the results that have been obtained, namely from 40 respondents who had a good attitude, namely 35 respondents (87, 5%) and 5 respondents (12.5%) had unfavorable attitudes